IMPLEMENTATION OF THE STUNTING PREVENTION AND REDUCTION POLICIES IN BONE DISTRICT - Resky Ahdyanti Putri; Novayanti Sopia Rukmana; Asri Nur Aina (Universitas Negeri Makassar, 2026)
This research aims to determine the success of implementing the Stunting Prevention and Reduction Policy in Bone Regency. This type of research is descriptive qualitative research with data collection techniques through observation, interviews and documentation. Meanwhile, checking the validity of the data is carried out through source triangulation. Data analysis techniques use data condensation, data presentation and drawing conclusions. The results of this research show that the implementation of stunting prevention and reduction policies in Bone Regency is based on Van Meter and Varn Horn (1975) policy indicators, namely: 1) Policy Standards and Targets 2) Resources 3) Characteristics of Implementing Organizations, 4) Communication between organizations related to activities, 5) The attitude of the implementers 6) The socio-economic and political environment, that in general the implementation of the policy has gone well, seen from the commitment of the Bone district government in overcoming the problem of preventing and reducing stunting through local strategies and regulations. The implementation of this policy is determined through regional regulations which regulate concrete steps to reduce stunting which are supported by legal certainty and transparency in its implementation obtained from the Health Service and other related agencies. In the last few years, the prevalence of stunting has decreased to 16%. The Bone Regency Government, through collaboration between departments and implementing parties, is expected to be able to reduce the stunting rate according to national standards at 14% so that the implementation of this policy reaches the community to achieve significant changes.